Rekonsiliasi dalam Tradisi Bela Menurut Teori Mirosla Volf pada Suku Dorit dan Teiwa, Mayarakat Madar, Kecamatan Pantar - Eunike Molebila; Joko Uil Pering; Yessy Mata (Jurnal Ilmiah Wahana Pendidikan, 2021)
Conflict is basically something that always exists and is difficult to separate in social life. Conflicts, whether occurring individually or in groups, are a common spectacle in social life. This arises as a result of the inability of humans to manage and deal with differences and diversity, both racial, ethnic and cultural diversity. Conflict usually does not just appear, but there are factors behind it. Conflicts can arise on different scales, such as conflicts between individuals (interpersonal conflict), conflicts between groups (intergroup conflict), conflicts between groups and the state (vertical conflict) and conflicts between countries (interstate conflict). Each scale has its own background and direction of development. Conflict itself is present as a manifestation of social, political, economic and cultural tensions or it can be caused by general feelings of dissatisfaction. If conflict can be managed and resolved properly by every element of society, it will have a good impact on the progress and change of society. On the other hand, if the conflict that occurs in the community is not able to be managed and handled properly, the conflict will have a negative impact, resulting in various damages, both physical and non-physical, insecurity, disharmony, and create instability, even resulting in casualties. This is what happened to the dorit and teiwa people in Madar Pantar District, East Nusa Tenggara. However, they also have a method or culture of reconciliation that can be a means of reconciling conflicts in their context, which is known as Bela. This research uses a qualitative descriptive method with the aim of seeing the concept of Bela as a means of reconciliation for the pantar dorit and teiwa tribes studied according to the theory of Misrosla Volf. Based on the results of the research, the stages of recognition and acceptance in the martial tradition correspond to and fulfill the reconciliation stages of Mirosla Volf's theory so that it can be a means of reconciliation for conflicts that occur in the two tribes